RETRATO DE Mª CRISTINA DE HABSBURGO, PINTURA INÉDITA DE JUAN LUNA NOVICIO - Gutiérrez García, María de los Angeles (Imafronte, 1993)
Juan Luna, Philippine painter settled down in Spain, was educated with the academy artist Alejo Vera. Since 1881, when he got a Second Class Medal in the National Exhibition of that year, his artistic life presents numerous ups and downs, due to his loss of prestige because of painting several oficial works. in 1889, durirlg his occasional stay in Murcia, the Province Coutlcil buyed one of his paintings: Retrato de la Reina Regente (Portrait of the Regent Queen). it is a hitherto unheard of piece, now preserved in the artistic fund of the Museum of Murcia Colleciion of Fine Arrs.